Conversion surgery for positive peritoneal washing cytology in pancreatic cancer - Mitachi, Katsutaka (BMJ Case Rep, 2019)
Positive peritoneal washing cytology (PPC) of pancreatic carcinoma is defined as distant metastasis in the American Joint Committee on Cancer or Union for International Cancer Control’s tumour, node, metastases classification. However, surgical resection was believed to be the only method that prolong survival; thus, many institutions perform pancreatectomy for PPC, despite the unfavourable prognosis. Therefore, a more preferable alternative treatment for PPC is required. A 64-year-old man with resectable pancreatic tail cancer presented to our hospital. PPC was detected at first laparotomy; thus, pancreatectomy was avoided and gemcitabine with nabpaclitaxel (GnP) was administered. After four courses of GnP treatment, PPC converted to negative, as evaluated by abdominal port cytology. Thus, distal pancreatectomy was performed, and R0 resection was achieved. He has been healthy for more than 24 months since the first laparotomy. Initial chemotherapy with the intention of converting the cytological status followed by surgical treatment might become a useful treatment strategy for PPC.